THE MODERATING ROLE OF GROSS DOMESTIC PRODUCT (GDP) IN THE RELATIONSHIP BETWEEN ECONOMIC GROWTH RATE AND TAX RATIO (The International Conference on Sustainable Economics Management and Accounting Proceeding, 2025)
This study aims to examine the moderating role of Gross Domestic Product (GDP) on the relationship between the economic growth rate and the tax ratio in Indonesia. Amidst persistent challenges in domestic revenue mobilization, this study hypothesizes that a larger economic capacity, proxied by the level of GDP, will strengthen the positive impact of economic growth on the tax ratio. Using annual time-series data from 2016 to 2022, this research employs Moderated Regression Analysis through a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The analysis results indicate that the proposed model is not a good fit for the existing data (R² = 0.020). Specifically, the findings show that neither economic growth nor GDP has a significant direct influence on the tax ratio. More importantly, the main hypothesis regarding the moderating role of GDP is not statistically supported. The primary contribution of this study is the empirical demonstration of a disconnect between macroeconomic growth and state revenue mobilization in Indonesia. This finding implies that the path towards a higher and sustainable tax ratio does not lie in passive reliance on economic growth alone, but rather on a path of deliberate, targeted, and fundamental institutional and administrative reforms to repair the existing fiscal transmission mechanisms.